PENGARUH METODE ABA (APPLIED BEHAVIOR ANALYSIS) TERHADAP KEMAMPUAN BERINTERAKSI SOSIAL ANAK AUTIS - Kriswilani .; Sumatri .; Feri Catur Yuliani (STIKES DUTAGAMA KLATEN, 2015)
Background: Autistic is a developmental disorder that affects some aspects of how children see the world and how to learn through experience. Children with autistic disorder usually less able to feel the social contact. Children with autism tend to be aloof and avoid contact with the surrounding environment. One method that is famous for teaching behavioral therapy is applied behavior analysis (ABA) therapy use a system that gives special training in children by providing positive reinforcement (reward / praise). Purpose: To determine the influence of ABA methods to social interaction skills of children with autism. Methods: Type of this research to be conducted in this study were pre-experimental research. With One group pretest posttest design. The population in this study were students from kindergarten to elementary school classes in the School of Autism BinaAnggita Yogyakarta as many as 10 children. This study uses total sampling technique. Respondent data collected using observation sheet ATEC. Analysis of the data used is using a paired t-test. Results: The results of this study are significant infuence that ABA therapy has an effect on the ability to interact socially autistic children. With the result that sig is 0,001 <0,05. Based on these results it is concluded that H0 is rejected and Ha accepted.